Selfish Corporations - Emanuele Colonnelli; Niels Joachim Gormsen (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2020)
We conduct representative large-scale surveys of U.S. citizens aimed at measuring perceptions of large corporations' environmental, social, and governance performance and investigate how these perceptions affect the public support for economic policies. The public demands corporations to behave better within society, a sentiment we label "big business discontent." We experimentally vary individual perceptions by showing animated videos that highlight the "good" and the "bad" of corporate behavior in recent years. We show that higher big business discontent lowers support for corporate bailouts. The effects are present across the whole political spectrum, but they are stronger for liberals than for conservatives, and they persist even a week after respondents viewed the videos. A second randomized experiment shows that simply making respondents think about the role of large corporations in society lowers their support for bailouts, highlighting a key mechanism whereby the public's pre-existing negative beliefs about big business influence behavior once these beliefs are manipulated or triggered. We conduct an additional experimental survey to show that individuals' self-reported policy preferences are reflected in costly behavioral actions. A higher big business discontent makes respondents less likely to sign an online petition or contact U.S. senators to support corporate bailouts. Treated respondents are also less likely to donate to a non-profit organization supporting the general interests of top U.S. executives. Together, our findings suggest that the perceived strength of the social contract between big corporations and their stakeholders may impact the public support for important economic policies.
Keywords: 330